Computational fluid dynamics modeling of rice husk combustion in a fluidised bed combustor - Taib, Mohd. Rozainee (Elsevier, 2010)
Computational fluid dynamics (CFD) modeling was carried out to determine the trajectories and residence time of burning rice husk particles in the fluidised bed combustor (FBC) at different secondary air flowrates. In FBC, the intra and extra-particle mass transfer resistance of the oxidising agent plays a major role in determining the combustion rate because of high temperature processing. Moreover, factors such as turbulence and retention time determine the reaction rate. In actual combustion experiments, these two factors could not be observed or determined distinctly, thereby hindering any further improvements in operating parameters or combustor design in order to maximise the efficiency of particle combustion. This hitch was solved through the application of (CFD) modeling. The modeling results offered significant insights into the trajectory and mass loss history of the rice husk particle combustion. The actual experimental results also showed agreement with the modeling results.